Comparison between carbon monoxide poisoning from hookah smoking versus other sources. (1st December 2020) - Nguyen, Vincent; Salama, Maha; Fernandez, Denise; Sperling, Jeremy D.; Regina, Angela; Rivera, Robert; Wang, Jessica; Friedman, Benjamin W.; Smith, Silas W.
Abstract: Introduction: Carbon monoxide exposure is a relatively unknown risk of smoking hookah. Dozens of cases of hookah-associated carbon monoxide toxicity have been described over the past decades, but smoking hookah is generally perceived as safe. Only recently have larger series of hookah-associated carbon monoxide toxicity been published. This study evaluates the incidence of hookah-associated carbon monoxide toxicity over 4 years, and compares the exposures from hookah against other carbon monoxide sources. Methods: This is a retrospective cohort study of all patients with carbon monoxide toxicity referred for hyperbaric oxygen therapy at an urban hyperbaric oxygen referral center from January 2015 through December 2018. Cases of hookah-associated carbon monoxide toxicity were compared to patients exposed to other carbon monoxide sources, with an analysis of patient comorbidities, symptomatology, and laboratory evaluation. Results: Over a 48-month period, 376 patients underwent hyperbaric oxygen therapy for carbon monoxide exposure. After exclusions, 265 patients with carbon monoxide toxicity from various sources were analyzed. There were 58 patients with hookah-associated carbon monoxide toxicity (22%). The proportion of hookah-associated carbon monoxide cases increased markedly in the latter years: 2015: 9.5%, 2016: 8.6%, 2017: 24.1%, 2018 41.6%. In the final 2 years analyzed, hookah smoking was the most frequent source of carbon monoxide toxicity referred for therapy. Hookah-associated carbon monoxide patients were younger (28.1 vs. 45.0 years, mean difference 16.8 years, 95% confidence interval: 11.5, 22.1 years, p < 0.001) and more likely to be female (60% vs. 46.6%, p = 0.06) than patients exposed to other carbon monoxide sources. The mean difference in carboxyhemoglobin concentration between hookah associated and those exposed to other carbon monoxide sources was 4.6% (mean 20.1% vs. 24.6%, 95%CI: 1.7, 7.5, p = 0.002). Conclusion: A substantial portion of patients with severe carbon monoxide toxicity was exposed through smoking hookah. The incidence of hookah-related carbon monoxide toxicity appears to be increasing.